2015
DOI: 10.1089/aid.2014.0211
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Viral Sequence Length and Number of Variable and Informative Sites in Analysis of HIV Clustering

Abstract: To improve the methodology of HIV cluster analysis, we addressed how analysis of HIV clustering is associated with parameters that can affect the outcome of viral clustering. The extent of HIV clustering and tree certainty was compared between 401 HIV-1C near full-length genome sequences and subgenomic regions retrieved from the LANL HIV Database. Sliding window analysis was based on 99 windows of 1,000 bp and 45 windows of 2,000 bp. Potential associations between the extent of HIV clustering and sequence leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…A greater extent of clustering for longer HIV sequences in this study corroborates the results of our recent study (93), which used a set of nearly full-length HIV-1C sequences from the LANL HIV Database (http://www.hiv.lanl.gov/). Longer HIV sequences are more informative for HIV cluster analysis due to a larger number of informative sites (93). The technique of long-range HIV genotyping allows the use of amplicon 1 and amplicon 2 sequences either separately or in concatenation for a powerful cluster analysis.…”
Section: Discussionsupporting
confidence: 90%
“…A greater extent of clustering for longer HIV sequences in this study corroborates the results of our recent study (93), which used a set of nearly full-length HIV-1C sequences from the LANL HIV Database (http://www.hiv.lanl.gov/). Longer HIV sequences are more informative for HIV cluster analysis due to a larger number of informative sites (93). The technique of long-range HIV genotyping allows the use of amplicon 1 and amplicon 2 sequences either separately or in concatenation for a powerful cluster analysis.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with our recent studies on sampling density (Novitsky et al, 2014) and importance of virus sequence length (Novitsky et al, 2015) in HIV cluster analysis. Two additional acute HIV sub-epidemics were found among clusters with 5+ members and bootstrap support between 0.70 and 0.80, although both of these clusters had low internode certainty.…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that bootstrapped ML inference of the short-range sequence set selected HIV lineages that represent only small sub-chains of much larger transmission chains in the population. Recently we demonstrated that viral sequence length plays an important role in HIV cluster analysis (Novitsky et al, 2015). It is likely that using long-range sequences could refine clustering and reveal more extensive clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not perform a bootstrapping analysis of the reconstructed trees, previous analyses have further demonstrated that support for groupings in the tree is increased when longer sequences are used, and clustering found in full-length datasets can be missed when using sub-genomic regions141516. Given the difficulty in generating and/or handling full genome datasets, our results demonstrate that gag - pol provides a dependable approximation; however it should be kept in mind that, at this point and considering we analysed a simulated dataset, the good performance of gag - pol could be more attributable to these genes’ combined length than to their particular characteristics.…”
Section: Discussionmentioning
confidence: 95%